Drop-On-Demand Lubrication of Gears: A Feasibility Study - Mirza, M.; Yilmaz, M.; Thieme, E.; Lohner, T.; Venner, C. H. (Frontiers in Mechanical Engineering, 2021)
Different lubrication methods, such as oil dip or injection lubrication, are used in gearboxes to lubricate tribological contacts and to dissipate frictional heat. To improve resource and energy efficiency, novel needs-based lubrication methods like the drop‑on‑demand lubrication are developed. Thereby, an ink-jet nozzle driven by a piezo element is used to generate picoliter droplets injected to tribological contacts. This study evaluates the feasibility of drop-on-demand lubrication of gears. Friction measurements in rolling-sliding contacts indicate the formation of typical elastohydrodynamic contacts. Power loss measurements of gears show a similar behavior compared to continuous minimum quantity lubrication. Hence, the study confirms that the operation of gears with drop-on-demand lubrication is possible. Moreover, it in-troduces the possibility of dynamic and flexible oil supply on a contact needs-based level.